Declining Physical Activity and Motivation from Middle School to High School - Dishman, Rod K. (Med Sci Sports Exerc, 2018)
PURPOSE: To determine whether naturally-occurring changes in intrinsic motivation, behavioral regulation, and goals mitigate declining physical activity among adolescents. METHODS: Latent growth modeling was applied in tests of change in intrinsic motivation, facets of behavioral regulation, and their interactions with goals on change in physical activity measured by accelerometer in a cohort of 260 boys and girls evaluated longitudinally from 6(th) through 9(th) grades. RESULTS: Physical activity declined less in youths who maintained higher intrinsic motivation or integrated regulation, but only when they maintained higher enjoyment goal compared to other students. Physical activity also declined less in students who maintained higher intrinsic motivation or integrated motivation and had bigger declines in appearance goal (or social and competence goals with intrinsic motivation) compared to students who maintained higher levels of those goals. The interactions correspond to 1 to 2 min per hour less decrease in physical activity. CONCLUSION: Consistent with Self-determination Theory, the findings encourage interventions that target autonomous motivation among youths. The results extend prior evidence in three ways. First, the cohort was tracked for three years using an objective measure of physical activity. Second, influences of intrinsic motivation and integrated regulation on changing physical activity were not direct. They interacted with changing goals, indicating that interventions should also focus on specific goals for physical activity as effect modifiers. Third, interventions focused on autonomous motivation should consider that controlled, introjected motivation may also interact with goals to influence on physical activity during the transition between middle school and high school.